2012
DOI: 10.3109/02699206.2012.734893
|View full text |Cite
|
Sign up to set email alerts
|

Role of sentence-final particles and prosody in irony comprehension in Cantonese-speaking children with and without Autism Spectrum Disorders

Abstract: English-speaking children with Autism Spectrum Disorders (ASD) are less capable of using prosodic cues such as intonation for irony comprehension. Prosodic cues, in particular intonation, in Cantonese are relatively restricted while sentence-final particles (SFPs) may be used for this pragmatic function. This study investigated the use of prosodic cues and SFPs in irony comprehension in Cantonese-speaking children with and without ASD. Thirteen children with ASD (8;3-12;9) were language-matched with 13 typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…Presumably TD subjects relied more on second-order mentalizing, therefore they perceived an impression of irony more often than ASD subjects, who have been shown to have a diminished tendency to use higher order mentalizing, but a relatively preserved tendency to rely on first-order mentalizing [ 53 , 54 ]. This consideration is in line with the results of previous studies on irony perception: all studies requiring second-order mentalizing processes [ 16 , 18 , 22 , 23 ] reported differences in irony perception between ASD and TD, while every study that did not report group differences [ 31 33 ] used tasks which could be completed using first-order mentalizing.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Presumably TD subjects relied more on second-order mentalizing, therefore they perceived an impression of irony more often than ASD subjects, who have been shown to have a diminished tendency to use higher order mentalizing, but a relatively preserved tendency to rely on first-order mentalizing [ 53 , 54 ]. This consideration is in line with the results of previous studies on irony perception: all studies requiring second-order mentalizing processes [ 16 , 18 , 22 , 23 ] reported differences in irony perception between ASD and TD, while every study that did not report group differences [ 31 33 ] used tasks which could be completed using first-order mentalizing.…”
Section: Discussionsupporting
confidence: 82%
“…assumptions about the beliefs another person has about the mental states of others [ 21 ]). In this regard it is very interesting to note that significant group differences with impairments in irony perception in ASD subjects have been uniformly observed in all studies that required at least second-order mentalizing processes [ 16 , 18 , 22 , 23 ]. Studies requiring only first-order mentalization processes to detect irony (e.g., based on identification of a mismatch between the mentalization of a person’s factual knowledge and their direct statements), however, partly confirmed significant impairments in ASD subjects [ 17 , 19 , 21 , 24 ] but partly failed to show clear cut differences between ASD and TD subjects [ 31 33 ].…”
Section: Introductionmentioning
confidence: 94%
“…While the majority of studies focuses on typical development, there is considerable evidence that children with different disorders struggle with the pragmatically complex task of understanding irony. For instance, children with Autism Spectrum Disorder tend to have more difficulties processing (Wang et al, 2006) and understanding ironic utterances than typically developing children (Happé, 1993;Li, Law, Lam, & To, 2013;Wang, Lee, Sigman, & Dapretto, 2006). Irony comprehension may also be impaired in children with Attention Deficit Hyperactivity Disorder (Caillies et al, 2014;Ludlow, Chadwick, Morey, Edwards, & Gutierrez, 2017), cerebral palsy (Caillies, Hody, & Calmus, 2012), Williams Syndrome, Prader-Willi syndrome and nonspecific mental retardation (Sullivan, Winner, & Tager-Flusberg, 2003).…”
Section: Ironymentioning
confidence: 99%
“…One explanation might be the complexity of the stimuli and task in the current test. In clinical samples, irony comprehension often been investigated in autism by written stories (34, 103, 104). However, in some studies using a more elaborated design patients with autism did not exhibit more difficulties in irony understanding than healthy controls did (105107).…”
Section: Discussionmentioning
confidence: 99%